Survival causal patterns of social and commercial entrepreneurial initiatives in Spain - Revuelto-Taboada, Lorenzo; Redondo-Cano, Ana; Balbastre-Benavent, Francisco (Journal of Business Economics and Management, 2021)
This research aims at analysing the influence of a holistic configuration of factors related to industry and the characteristics of the entrepreneur and the business, on the survival of social and commercial entrepreneurial initiatives in both, new and consolidated companies. The sample ranges from 2,851 to 2,109 firms, according to the period considered, and has been obtained from the reports of the projects submitted to the Assistance Programme to Young Entrepreneurs, promoted by the Valencian Institute of Youth. Other sources of information have been the Institute’s own reports and the Chambers of Commerce. A configurational analysis is performed using the Fuzzy-Set Qualitative Comparative Analysis. The results obtained show that there is no necessary condition by itself and that there are several sufficient solutions that explain a considerable percentage of survival cases. They also show how the solutions vary significantly and, consequently, the relevance of the different causal antecedents, when the company acquires greater maturity.